A quantitative evaluation of the high elbow technique in front crawl - Suito, H.; Nunome, H.; Ikegami, Y. (Journal of Sports Sciences, 2017)
Many coaches often instruct swimmers to keep the elbow in a high position (high elbow position) during early phase of the underwater stroke motion (pull phase) in front crawl, however, the high elbow position has never been quantitatively evaluated. The aims of this study were (1) to quantitatively evaluate the "high elbow" position, (2) to clarify the relationship between the high elbow position and required upper limb configuration and (3) to examine the efficacy of high elbow position on the resultant swimming velocity. Sixteen highly skilled and 6 novice male swimmers performed 25 m front crawl with maximal effort and their 3-dimensional arm stroke motion was captured at 60 Hz. An attempt was made to develop a new index to evaluate the high elbow position (Ihe: high elbow index) using 3-dimensional coordinates of the shoulder, elbow and wrist joints. Ihe of skilled swimmers moderately correlated with the average shoulder internal rotation angle (r = -0.652, P < 0.01) and swimming velocity (r = -0.683, P < 0.01) during the pull phase. These results indicate that Ihe is a useful index for evaluating high elbow arm stroke technique during the pull phase in front crawl.